2015
DOI: 10.4172/2167-0250.1000133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Low Dose and High Dose Antioxidants along with Antibiotics in Idiopathic Oligo, Astheno and Oligoasthenospermia

Abstract: Objective: The aim of this study was to explore the efficacy of low dose and high dose antioxidants for the treatment of idiopathic oligiospermia, asthenospermia and oligoasthenospermia. Materials and methods:This prospective quasi experimental study was conducted in Infertility Care and Research Center (ICRC) Ltd, Dhaka, Bangladesh between January 2013 and December 2014. Eighty four patients were the target population for this study. After thorough investigations those patients were diagnosed as idiopathic ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Methylcobalamine (750 mg), Co-Enzyme Q 10 (2.5 mg), Lycopene (2 mg, Folic acid (1.5 mg), L-Arginine (10 mg), L-Carnitine tartarate (50 mg), Iron (5 mg), Zink (7.5 mg), Copper (1 mg), Manganese (2 mg), Selenium (100 mcg), Pyridoxyl hydrochloride (5 mg), Glutathionine (2.5 mg). Results show a significant improvement in sperm count and in total and progressive motility in 79% of patients under Oligocare treatment that based on the use of a mixture of multivitamins and micronutrients as basic antioxidant elements [17].…”
Section: Parametermentioning
confidence: 98%
See 2 more Smart Citations
“…Methylcobalamine (750 mg), Co-Enzyme Q 10 (2.5 mg), Lycopene (2 mg, Folic acid (1.5 mg), L-Arginine (10 mg), L-Carnitine tartarate (50 mg), Iron (5 mg), Zink (7.5 mg), Copper (1 mg), Manganese (2 mg), Selenium (100 mcg), Pyridoxyl hydrochloride (5 mg), Glutathionine (2.5 mg). Results show a significant improvement in sperm count and in total and progressive motility in 79% of patients under Oligocare treatment that based on the use of a mixture of multivitamins and micronutrients as basic antioxidant elements [17].…”
Section: Parametermentioning
confidence: 98%
“…In recent years, recourse to the use of micronutrients and vitamins as antioxidants treatment in infertile men has been strongly recommended. So, several reviews of clinical studies addressing the effect of oral antioxidants supplementation (vitamins C, B 12 and E, zinc, selenium, magnesium, arginine folate, carnitine and carotenoids) on sperm quality and pregnancy rate in infertile men have been published recently [14][15][16][17]. It found that a woman was more likely to have a pregnancy or live birth if her male partner took certain vitamins or other antioxidants [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation